Adhesion of ADP-activated Platelets to Intact Endothelium under Stagnation Point Flow In Vitro Is Mediated by the Integrin αIIbβ3 - Reininger, Armin J.; Korndörfer, Markus A.; Wurzinger, Laurenz J. (Thrombosis and Haemostasis, 1998)
As we demonstrated earlier, platelets adhere to intact endothelium provided they are activated and convectively transported against the endothelial surface. To identify the platelet receptors involved we superfused cultured endothelium with activated platelet rich plasma (PRP) by means of the Stagnation Point Flow Adhesio- Aggregometer while blocking various platelet receptors. Inhibition was performed with the tetrapeptide RGDS, the non-peptide Ro-43-8857, or a monoclonal antibody directed against integrin αIIbβ3. Platelet deposition was video-recorded and quantified by image analysis. Infusion of RGDS or Ro-43-8857 into ADP-stimulated PRP completely prevented adhesion as well as subsequent aggregation. Interrupting the inhibitor infusion while ADP stimulation persisted, prompted adhesion and aggregation, demonstrating the reversibility of the inhibition. Platelet adhesion was irreversibly blocked by preincubation of the PRP with the moab against αIIbβ3. Its specific binding was confirmed by immuno-electron microscopy. Our results suggest that platelet adhesion to intact endothelium is mediated via platelet integrin αIIbβ3.